A new species of Eumops (Chiroptera: Molossidae) from southwestern Peru - Medina, César E.; Gregorin, Renato; Zeballos, Horacio; Zamora, Hugo T.; Moras, Ligiane M. (Zootaxa, 2014)
The genus Eumops is the most diverse genera of molossid bats in the Neotropics. In Peru this genus is widely distributed and represented by nine species: E. auripendulus, E. delticus, E. hansae, E. maurus, E. nanus, E. patagonicus, E. perotis, E. trumbulli, and E. wilsoni. After several years of mammalian diversity surveys in the coastal desert and western slopes of southwestern Peru, a specimen of Eumops was collected whose unique set of traits allows us to assert that deserves to be described as a new species. Based on molecular and morphological evidence, the new species is related to medium-large sized species (i.e. E. glaucinus, E. auripendulus, and E. perotis). Cytochrome b genetic divergence between the new species and the other species of the genus was high (> 12%) and it is consistent with morphological divergence presented for this new species. This new species, endemic to Peru, increases the diversity of Eumops to 16 species.